PELAKSANAAN PELAYANAN PUBLIK DI KECAMATAN PUCUK RANTAU KABUPATEN KUANTAN SININGI - Sihornas, Raja; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is motivated by the lack of maximum service provided of PucukRantausub-district officeof KuantanSingingi Regency to the societyand also high quality ofclaim public services to the sub-district office. Although this claimis often do not matchwith the expectations. Empirically, public services still characterized by a complicated,slowly, expensive and tiring. There are many kinds of public service business in thePucukRantau sub-district office is often reaped protests such as less effective andefficient of these services.The purpose of this research is to know the implementation ofpublic service PucukRantau sub-district office in KuantanSingingi regency, besides thatto know the factors inhibiting the implementation of public service at the sub-districtoffice of PucukRantau in KuantanSingingi Regency. In this research the writers was usedescriptive qualitative research methods, this research method aims to analyze andillustrated how the implementation of society services in the sub-district officeofPucukRantau in KuantanSingingi regency. In this study the subject is the official andthe society were conduct service activities while the object of study is theimplementation of PucukRantau office in providing services to the society. In thisresearch there is a plan of thought as a reference in developing problems to theresearchers, the space of service is based on the principle of good service proposed bySinambela.The result of the study is found that public service inPucukRantau HeadOffice still needs to be improved, both in terms of Human Resource and in terms ofcompleteness of facilities and infrastructure in implementing public services, so thatwhat people expect in PucukRantau District will be realized. One of the issues that needto be paid attention in the Office of PucukRantau head is the professionalism ofemployees to be more disciplined in carrying out duty as a service provider to thepublic.Keywords: implementation, Service, Public